Crossroads of demography - Devedžić Mirjana (Stanovništvo, 2013)
This paper is dedicated to the 50th anniversary of the Stanovništvo (Population) journal, launched by the Center for demographic research in Belgrade in 1963. The anniversary is an opportunity to reflect on developments and trends in demography as a discipline, thus the paper points out certain specifics of these developments. The specifics discussed mirror the author's choice, which was guided primarily by the criterion of interestingness, but also by the intention to make a survey. Hence points about the development of demography are backed by insights made by a number of other demographers. The major source of references were papers and speeches given on similar occasions - anniversaries of journals, anniversaries of associations of demographers, as well as special issues of journals dedicated to theory and methodology. Certain points are also made based on other sources of reference. The major part of the paper is related to transformations of demography, which has started as a predominantly formal discipline and has developed into a social and interdisciplinary field. Topical and methodological expansion of demography induces mixed reactions among demographers. Ones welcome its diversification, whereas others see such changes as signs of abandoning the essence of demography. This makes it harder and harder to define the area of demographic research. Changes in demography are mostly studied from the standpoint of polarized dimensions: quantitative-qualitative, macro-micro, and, in the context of diversification, formal demography vs. population studies. Another important segment of development trends in demography is that of improving its vocabulary, which is affected by other fields related to demography. Terminological changes are also related to the specification of certain branches and subfields of demography. For instance, anthropological and spatial demography have roots in earlier development phases of demography. Still, these terms have become popular at a later stage, only when the methodological and cognitive capacities of the corresponding research approaches have increased. The paper also indicates that demographers do not find new inspiration only outside of the core demographic problems. As an example, man fertility is briefly discussed as an increasingly popular topic in literature during the last decade. Finally, attractive presentation of demographic content is found to be very important for visibility and applicability of demography, which is illustrated by interpreting some of the most frequently videos related to demography on YouTube. The paper concludes that different paths that open during the development of demography are not incompatible, that they represent demographers' diverse choices, and that they all contribute to strengthening the field. [Projekat Ministarstva nauke Republike Srbije, br. III 47006: Istraživanje demografskih fenomena u funkciji javnih politika u Srbiji]